PREVALENCE OF SGLT2 INHIBITOR AND GLP-1 RECEPTOR AGONIST PRESCRIPTIONS IN PATIENTS WITH COMORBID DIABETES AND CARDIOVASCULAR DISEASE IN RAJAVITHI HOSPITAL - Srisuk, Thitiporn (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION The clinical relevance of sodium-glucose co-transporter 2 inhibitors (SGLT2i) and Glucagon-like peptide 1 receptor agonists (GLP-1 RA) has been rapidly evolving for the treatment of type 2 diabetes mellitus (T2DM), especially in patients with cardiovascular comorbidities. There is a lack of global data on the prescription prevalence of these medications. The primary objective of this study was to estimate the prevalence of SGLT2i and GLP-1 RA prescriptions in patients with comorbid diabetes and cardiovascular disease in Rajavithi Hospital from 2017 to 2020. Another objective was to further characterize the patients regarding demographic, clinical parameters, and other medication usage between patients who were and were not prescribed SGLT2i and/or GLP- 1 RA. METHODOLOGY Data were collected from adults with comorbid diabetes and cardiovascular disease managed in Rajavithi Hospital, Thailand between January 1, 2017, and December 31, 2020. The prevalence of SGLT2i and GLP-1 RA prescriptions was estimated. Demographic, clinical parameters, and other medication usage between patients who were and were not prescribed SGLT2i and/or GLP-1 RA were reported in the percentages or mean ± standard deviations depending on the type of variable data. RESULTS Of the 1114 participants with T2DM and cardiovascular comorbidities, 567 were female (50.9%), mean age of 69.6 years (SD 12.4), mean HbA1c 7.2% (SD 1.8) and 607 (54.5%) were obese. Within the period, the prevalence of SGLT2i and GLP-1RA prescriptions were 4.4% and 1.3% respectively. Most of these medications were prescribed by cardiologists (60.3%) and endocrinologists (39.6%). The prescription rate of these medications was low even if the rate of SGLT2i prescription has increased dramatically in 2020 (p = 0.003) CONCLUSION The prescription rates of SGLT2 inhibitors and GLP-1 receptor agonists were low, especially in type 2 diabetes mellitus patients with cardiovascular comorbidities, even with a proven benefit of reduced morbidity and mortality from cardiovascular events. These medications should be considered to be prescribed in high-risk patients to improve cardiovascular outcomes independent of A1C.